Bilateral renal cortical necrosis following abdominal surgery - Chothia, MY; Bates, WD; Davids, MR (African Journal of Nephrology, 2017)
A 58-year-old patient developed complete anuria following elective abdominal surgery for an ileocaecal mass. Contrast-enhanced computed tomography demonstrated absent intra-renal blood flow and a kidney biopsy confirmed diffuse cortical necrosis. Histology of the ileocaecal mas displayed deep fissuring which was diagnostic of Crohn’s disease. Bilateral renal cortical necrosis (BRCN) is a rare complication of surgery but should be considered in any patient developing complete anuria. Since the disease is often associated with a coagulopathy, conditions predisposing to thrombosis should be sought. Inflammatory Bowel Disease (IBD) with surgical complications, as in this case, should be considered among the conditions which may predispose to BRCN.